Experience in Poverty Reduction in the World and Lesson for Vietnam - Dang Huu Dung (Randwick International of Social Science Journal, 2021)
Vietnam is a country that is considered to have certain successes in poverty reduction. However, poverty is still very concerned and is always one of the hot issues of society. Through the study of documents, this article aims to learn about effective poverty reduction activities of countries around the world so that we can learn from the experiences, good lessons of these countries to apply in reducing effectively poverty in Vietnamese. The results of the literature review show that poverty reduction should rely on the internal resources of the community and the active participation of the poor. In addition, the support of professionals such as social workers is also one of the core factors for success in effective and sustainable poverty reduction.